Is Village-Level Microfinance Beneficial at the Community, Enterprise and Household Levels? A Case Study from Indonesia - Ahmad Rifai; Koi-Nyen Wong; Soo-Khoon Goh (International Journal of Business and Society, 2021)
The local governments of the Riau Province of Indonesia had been given the mandate to use UED-SP as a microfinance programme to serve the financial needs of the rural poor, to promote rural economic activities and to create employment opportunities. Despite the village-level microfinance programme was able to accomplish rural outreach with financial sustainability (Rifai et al., 2019), there is limited evidence to validate its real impact on the rural MFI participants at three different levels of village development. The findings reveal that microloans appear to have positive impacts on the microfinance participants at the community level, at the level of micro-enterprise and at the household level. The rural MFIs should be targeting this village segment of the rural poor, while the local governments should provide the support to warrant deeper outreach.